Using Herbal dyes as an alternative staining method for sperm evaluation. Issue 3 (23rd April 2020) - Ebrahimi, Mohammadreza; Parham, Abbas
Abstract: Staining, as a valuable method for sperm morphological assessment, has been used to determine sperm abnormalities, fertilization capability and sperm suitability during freezing‐thawing process. Synthetic dyes have been used for sperm viability and morphological evaluation. However, most of them have been made from chemical substances and have a perilous effect on the environment. In the current study, we evaluated three different natural dyes as the natural sources of dye for sperm staining. Bull frozen semen was used and prepared on slides for staining. Aqueous extract dye of black mulberry (BM), henna (HA), safflower (SA) and eosin‐nigrosine (control group) were used for sperm staining. Additionally, the effect of staining dyes on viability and some morphological parameters (head area: HR, head abnormality: HB and tail abnormality: TA) were evaluated. Although none of the natural dyes could detect viability of the sperm cells, safflower stain (HR: 26.55 µm, HB: 0% TA: 28%) and black mulberry stain (HR: 25.07 µm, HB: 2% TA: 3%) compared to control group (HR: 34.29 µm, HB: 4%, TA: 4%) provoked a strong reaction in the sperm cells, so that the sperms were observed yellow and red respectively. The reaction of sperm cells to the henna dye was very poor and it did not stain the sperm cells. Thus, the present study demonstrated that SA and BM dyes are able to stain the spermatozoa and with further modification could be used as alternative dyes for sperm staining in the study of sperm morphology, but not viability. Staining with these dyes can be an alternative to current costly chemical staining methods. Abstract : In this study, we assessed the validity of some herbal dyes including black mulberry (BM), henna (HA) and safflower (SA) for sperm evaluation. Our results revealed that SA and BM dyes are able to stain the spermatozoa and could be used as alternative dyes for sperm staining in the study of sperm morphology.